2016
DOI: 10.2106/jbjs.15.01133
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Surgical Field with Propionibacterium acnes in Primary Shoulder Arthroplasty

Abstract: P. acnes is likely to be spread throughout the surgical field from the subdermal layer via soft-tissue handling by the surgeon and instruments. Strategies need to be utilized to minimize this contact and to reduce the chance of colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 18 publications
6
52
1
Order By: Relevance
“…It is the most common bacterium found in the deep tissues at the time of revision shoulder arthroplasty performed for pain, stiffness, and component loosening (3). Because common skin preparations and antibiotics given around the time of surgery fail to completely eradicate the bacteria (5)(6)(7)(8)(9), particularly those under the skin surface, transection of the dermal structures can lead to inoculation of C. acnes (and related Cutibacterium species) into the deeper tissues and implants at the time of the original shoulder arthroplasty (10,11). Over time, these slow-growing bacteria are believed to be responsible for arthroplasty failure resulting in a need for a revision surgery.…”
mentioning
confidence: 99%
“…It is the most common bacterium found in the deep tissues at the time of revision shoulder arthroplasty performed for pain, stiffness, and component loosening (3). Because common skin preparations and antibiotics given around the time of surgery fail to completely eradicate the bacteria (5)(6)(7)(8)(9), particularly those under the skin surface, transection of the dermal structures can lead to inoculation of C. acnes (and related Cutibacterium species) into the deeper tissues and implants at the time of the original shoulder arthroplasty (10,11). Over time, these slow-growing bacteria are believed to be responsible for arthroplasty failure resulting in a need for a revision surgery.…”
mentioning
confidence: 99%
“…A perceived weakness of this study design is the apparent lack of a control comparator, to determine the incidence of P. acnes in the subdermal without the use of the wound protector drape. Our justification for this is that several studies have already reported the incidence of P. acnes in the subdermal layer and given that our incidence of 23% (positive swabs of the subdermal layer) correlates with those published data, we consider this to be an acceptable comparator.…”
Section: Discussionmentioning
confidence: 74%
“…It is a common contaminant in shoulder surgery, and a potential pathogen in post‐operative shoulder infections . Recent studies indicate a high incidence of P. acnes in the subdermal layer, and it is postulated that the organism may be carried into the deeper tissues during surgery by instruments or by hand …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations